To what extent does a lack of refrigeration of generic chloramphenicol eye-drops used in India decrease their purity and what are the implications for Europe?. Issue 5 (25th April 2008) - Aboshiha, J; Weir, R; Singh, P; Ewings, P; Lovering, A
Abstract : Background/aims: Thermal degradation of chloramphenicol occurs at a faster rate when stored in unrefrigerated conditions. This study measures the concentration of the principal thermal breakdown product of generic chloramphenicol eye-drops being sold over the counter in chemists in different locations in India. Methods: Forty-eight samples of generic chloramphenicol eye-drops were collected form Delhi and Chennai (Madras) in India. Conditions of storage of chloramphenicol eye-drops were recorded at the time of purchase. Concentrations of a hydrolytic degradation product of chloramphenicol were measured using validated high-pressure liquid chromatography. Results were compared with accepted UK standards. Results: Significantly higher levels of chloramphenicol thermal breakdown product were found in collected samples. All samples purchased were being stored in unrefrigerated conditions in the chemists sampled. Shelf lives exceeded UK equivalents, varying considerably between manufacturers. Conclusion: Inadequate refrigeration and prolonged shelf lives of chloramphenicol generics collected from Delhi and Chennai are associated with very high levels of chloramphenicol thermal breakdown product. These levels substantially exceed UK quality-assurance standards undermining product reliability, possibly contributing to the positive selection of resistant organisms and product toxicity effects. The principals of quality-assurance breakdown described are particularly relevant to Europe, following recent deregulation of chloramphenicol eye-drops purchased over the counter.